2020
DOI: 10.1038/s41598-020-59106-z
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Activation in Zebrafish Heart Regeneration

Abstract: Autophagy is an evolutionarily conserved process that plays a key role in the maintenance of overall cellular health. While it has been suggested that autophagy may elicit cardioprotective and pro-survival modulating functions, excessive activation of autophagy can also be detrimental. In this regard, the zebrafish is considered a hallmark model for vertebrate regeneration, since contrary to adult mammals, it is able to faithfully regenerate cardiac tissue. Interestingly, the role that autophagy may play in ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 79 publications
2
21
1
Order By: Relevance
“…Immunoblot analysis of endogenous LC3 did not reveal clear differences in the abundance of lipidated LC3-II between wt , heterozygous and homozygous atg13 mutants under basal conditions and in response to BafA1 treatment (Figure 2C). In contrast to human or rodent samples, zebrafish appear to show higher basal lipidated LC3-II levels from 2dpf 55, 6769 , which could be due to differences in LC3 processing, and we observed a similar pattern even in the absence of atg13 expression. More informative, however, was the analysis of the autophagy receptor protein p62 (SQSTM1), which is degraded by the autophagy machinery, and is thus a good measure of flux.…”
Section: Resultscontrasting
confidence: 47%
“…Immunoblot analysis of endogenous LC3 did not reveal clear differences in the abundance of lipidated LC3-II between wt , heterozygous and homozygous atg13 mutants under basal conditions and in response to BafA1 treatment (Figure 2C). In contrast to human or rodent samples, zebrafish appear to show higher basal lipidated LC3-II levels from 2dpf 55, 6769 , which could be due to differences in LC3 processing, and we observed a similar pattern even in the absence of atg13 expression. More informative, however, was the analysis of the autophagy receptor protein p62 (SQSTM1), which is degraded by the autophagy machinery, and is thus a good measure of flux.…”
Section: Resultscontrasting
confidence: 47%
“…although the protection of iPostc on myocardial I/R injury has been confirmed, the underlying mechanisms in senescent myocardium are still unclear. autophagy is a vital physiological process in cells, which is considered the key to maintaining the normal structure and function of the heart (30). it has been reported that autophagy plays a dual role in myocardial i/r, low levels of autophagy can relieve energy depletion, maintain protein homeostasis, remove damaged cells and play a protective role in cell survival during ischemia (31), but long-term upregulation of autophagy can lead to excessive cell degradation and death (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BCAAs stimulate mTOR activation which promotes metabolic reprogramming to glycolysis from fatty acid oxidation through HIF-1α (92). In contrast, inhibition of mTOR promotes human iPSC-derived cardiomyocyte maturation and impairs zebrafish heart regeneration following injury (93,94). mTOR is also inhibited by 5′ adenosine monophosphate-activated protein kinase (AMPK) through tuberous sclerosis complex 2 (TSC2) (95).…”
Section: Amino Acid Metabolism In the Heartmentioning
confidence: 99%